HYGIENIC TRAINING AND EDUCATION OF CHILDREN OF PRESCHOOL AGE IN PRESCHOOL EDUCATIONAL INSTITUTIONS - A.Z. Garifullina (Ukrainian Medical Stomatological Academy, 2016)
Introduction. Health education of children, mostly covers children preschool age and health education young children, junior and middle school age mainly lies with the teachers and parents, which is not always successful. Sanitary training of kindergarten is a mere formality. Based on the foregoing, we set a goal: to increase the effectiveness of prevention of dental disease in preschool children by improving the system of hygiene training and education. Material and methods. A dental examination organized by 225 children from 3 to 5 years living in the city of Omsk. Determining the level of formation of hygienic habits for oral care was carried out by studying them in the questionnaires, interviews and children in special cases. To investigate the role of motivation of preschool children to hygienic education, as well as the level of hygiene knowledge questionnaire was conducted interviewing parents, caregivers and healthcare professionals. Statistical processing of materials research was carried out using the difference method, χ² - criterion. The Results. Comparing the effectiveness of different methods of hygienic training and education in preschool children may be noted that in conducting hygiene training and education developed by the author's method of caries reduction of growth was 46.5% Conclusion. In the developed technique is the gradual formation of habits of oral hygiene, and as a consequence: the more funds used for hygiene education and upbringing of children, the better and better is the formation of habits.